Influence of biochar remediation on Eisenia fetida in Pb-contaminated soils. (May 2022) - Sun, Fengfei; Chen, Junfeng; Chen, Fengyun; Wang, Xu; Liu, Kai; Yang, Yuewei; Tang, Meizhen
Abstract: In this study, the remediation influence of maize straw biochar on earthworms ( Eisenia fetida ) in contaminated soils (with Pb at 0, 300, 700, and 1000 mg kg −1 ) amended with different amounts of biochar (0%, 1%, 3%, and 5%) was investigated. The results showed that applying biochar to metal-polluted soils effectively reduced the mobility of Pb, promoting the transformation of Pb from exchangeable (EXC) and bound-to-carbonate (Carb) fractions to Fe/Mn oxide (FeMnOx), organic bound (ORG) and residual (RES) fractions. Consequently, a reduction in the mortality and weight loss of earthworms was also achieved by biochar. The accumulation amount of Pb in earthworms steadily increased with exposure time, and with the increasing dosage of biochar, the accumulated Pb decreased by 50.8–78.0% (300 mg kg −1 ), 30.9–67.3% (700 mg kg −1 ), and 17.4–55.1% (1000 mg kg −1 ), which was significantly positively correlated with the mortality of earthworms. Simultaneously, the application of biochar increased the soil pH (0.05–0.23 units), cation exchange capacity (CEC) (0.26–4.54 cmol kg −1 ), and content of organic matter (0.54–11.66%). There were higher soil enzyme activities (including sucrase activity, urease activity, and alkaline phosphatase activity) in the treatments with a biochar addition of 3%. Through remediation, Proteobacteria (50.82%), Actinobacteriota (32.37%), Firmicutes (4.83%) and Bacteroidota (1.88%) were the most important phyla in the microbiota communities. Furthermore, soil pH value and leaching toxicity concentration showed the most striking effects on earthworms. Therefore, the influence of earthworms must be taken into account in the remediation of Pb-contaminated soil with biochar. Graphical abstract: Image 1 Highlights: Biochar can efficiently immobilize Pb in contaminated soil. Biochar improved soil properties and increased soil enzyme activities (3%). Biochar decreased mortality, weight loss and Pb accumulation in earthworms. Proteobacteria, Actinobacteriota, Firmicutes and Bacteroidota major microbial phyla.